MEDIUL INOVATOR DE ÎNVĂȚARE ȘI BIBLIOTECILE - KULIKOVSKI, Lidia (BIBLIOPOLIS, 2020)
Lately it is talking insistently about the library as an innovative learning environment. The article published in the blog „Open universe” of Salamanca University library. This concept is actual for the Republic of Moldova too, in the context of Novateca Program activity. Almost all the district libraries have modern Learning Centre, the „B.P. Hasdeu” Municipal Library – a Center for librarians, The National Library – center for statistics, a new center will be open at the Children National Library. The article explain what is an innovative learning environment, its features and functions.